Manuscript Diversity, Meaning, and Variance in Juan Manuel's El Conde Lucanor. - De Looze, Laurence N. (University of Toronto Press, 2014)
De Looze's complex and nuanced reading sheds new light on an important work and makes a significant contribution to medieval studies, Spanish studies, and the history of the book.